2012
DOI: 10.7860/jcdr/2012/4339.2618
|View full text |Cite
|
Sign up to set email alerts
|

Purpura Fulminans in a Child: A Case Report

Abstract: Purpura Fulminans is a life threatening condition characterised by cutaneous haemorrhage and gangrenous necrosis. We present such a case in an eight year old child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…We performed a Medline search to identify any related articles using the key words "purpura fulminans" and "P. aeruginosa". As a result, we found two reports: one by Lerolle et al and one by Aroor et al [7,8] Lerolle et al reported the results of fluorescence confocal microscopy, which showed P. aeruginosa in the dermal vessels of a deceased patient with purpura fulminans. [7] Microorganisms were typically identified inside the capillaries in foci with multiple bacteria in the purpuric skin.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We performed a Medline search to identify any related articles using the key words "purpura fulminans" and "P. aeruginosa". As a result, we found two reports: one by Lerolle et al and one by Aroor et al [7,8] Lerolle et al reported the results of fluorescence confocal microscopy, which showed P. aeruginosa in the dermal vessels of a deceased patient with purpura fulminans. [7] Microorganisms were typically identified inside the capillaries in foci with multiple bacteria in the purpuric skin.…”
Section: Discussionmentioning
confidence: 76%
“…reported an eight-year-old boy who presented with a fever and purpuric rash involving all four limbs. [8] Their patient eventually developed gangrene of all digits and the pinna, and the condition deteriorated progressively until he was discharged against medical advice in a moribund state. In that case, the blood culture grew P., but whether or not it was P. aeruginosa was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is convenient to think about other etiological possibilities. 6 The characteristic lesions of purpura fulminans are erythematous lesions greater than 2 mm until their color turn purplish on the center, which does not disappear upon acupressure. They are indurated, painful with palpation and secondary to capillary extravasation, progressing to necrosis and with the presence of thrombosis in the microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…PF is a rare, life-threatening disorder of acute onset skin lesions due to disseminated intravascular coagulopathy (DIC) and small vessel thrombosis of the dermis, which is characterized by hemorrhagic infarction of skin (8). DIC triggers systemic activation of blood coagulation resulting in excessive blood clotting, which leads to endothelial injury.…”
Section: Discussionmentioning
confidence: 99%